Developmental regulation of RNA processing by Rbfox proteins - Conboy, John G. (Wiley Interdiscip Rev RNA, 2016)
The Rbfox genes encode an ancient family of sequence-specific RNA binding protein (RBP) that are critical developmental regulators in multiple tissues including skeletal muscle, cardiac muscle, and brain. The hallmark of Rbfox proteins is a single high-affinity RRM domain, highly conserved from insects to humans, that binds preferentially to UGCAUG motifs at diverse regulatory sites in pre-mRNA introns, mRNA 3′UTRs, and pre-miRNAs hairpin structures. Versatile regulatory circuits operate on Rbfox1 pre-mRNA and mRNA to ensure proper expression of Rbfox1 protein isoforms, which then act on the broader transcriptome to regulate alternative splicing networks, mRNA stability and translation, and microRNA processing. Complex Rbfox1 expression is encoded in a large gene encompassing multiple promoters and alternative splicing options that govern spatiotemporal expression of structurally distinct and tissue-specific protein isoforms with different classes of RNA targets. Nuclear Rbfox1 is a candidate master regulator that binds intronic UGCAUG elements to impact splicing efficiency of target alternative exons, many in transcripts for other splicing regulators. Tissue-specificity of Rbfox-mediated alternative splicing is executed by combinatorial regulation through the integrated activity of Rbfox proteins and synergistic or antagonistic splicing factors. Studies in animal models show that Rbfox1-related genes are critical for diverse developmental processes including germ cell differentiation and memory in Drosophila, neuronal migration and function in mouse brain, myoblast fusion and skeletal muscle function, and normal heart function. Finally, genetic and biochemical evidence suggest that aberrations in Rbfox-regulated circuitry are risk factors for multiple human disorders, especially neurodevelopmental disorders including epilepsy and autism, and cardiac hypertrophy.